Nano-Magnetic Catalyst CaO-Fe3O4 for Biodiesel Production from Date Palm Seed Oil - Mortadha A Ali; Imad A. Al-Hydary; Tahseen A Al-Hattab (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
A nanocatalyst of CaO supported by Fe3O4 magnetic particles was prepared by a chemical precipitation method. It was characterized by various techniques including X-ray diffraction, transmission electron microscopy (TEM), scanning electron microscopy (SEM); Fourier transforms infrared spectroscopy (FTIR), and Hammett indicator. It has been found that the catalyst consists of CaO and Fe3O4 accompanied by CaFe2O4. This composite catalyst was used for the catalytic transesterification of palm seed oil. The results revealed that the highest biodiesel yields for palm seed oil of 69.7% can be obtained under the conditions of (65 °C reaction temperature, 300 min reaction time, 20 methanol/oil molar ratio, and 10 wt.% of CaO/Fe3O4 catalyst loading). The physicochemical properties of the biodiesel produced from palm seed oil were further studied and compared with the ASTM and the EN biodiesel specifications. The results showed that the properties of the biodiesel produced comply with the international standard specifications.